An example of subtle intertextuality - Marinčič, Katarina (Vestnik za tuje jezike, 2025)
The topic of this article is intertextuality in the novel Telling Tales by the British writer Anne Cleeves. Cleeves is one of the most successful contemporary authors of crime novels. She owes part of her fame to high-profile television adaptations of the Shetland and Vera series. However, her novels are not only cleverly crafted stories to suit a wide audience; they also cater for more sophisticated readers. In this article, we aim to show the multilayered nature of her writing by using the example of Telling Tales, a novel that is interwoven with thematic and even formal allusions to Flaubert’s Madame Bovary, although a reader who is not susceptible to intertextuality can enjoy the plot and denouement of a crime story even without it. Similarly, intertextual clues are easily missed in the television adaptation of the novel. But for the reader who catches the intertextual clues, they are certainly an enrichment. Anne Cleeves uses them as a means of psychological characterization, but they also serve as a starting point for reflection on reading. The author, who believes in the importance and even the therapeutic value of reading, allows for the possibility of a “bad”, harmful reading and reflects on it through the story of a side character whose attitude to books and life is reminiscent of Flaubert’s heroine.
Keywords: angleška književnost; branje; Cleeves, Ann; Flaubert, Gustav; francoska književnost; intertextuality; medbesedilnost; reading